Investigation of taxonomic shrub resources in Qiqihar and analysis of their economic potentiality - CUI Lin; ZHANG Qiang; WANG Ligang; ZHANG Yuzhu; HAN Qin; JIANG Xiancui (Xibei zhiwu xuebao)
[Objective] The study aims to find out the shrub resource situation and its economic potentiality in Qiqihar, and provide basis for the development and utilization of shrub resources in this area. [Methods] The species composition, distribution, and economic potentiality were analyzed by combining literature review, sampling line, and sampling square survey. [Results] There were 185 species of shrubs, which belonged to 57 genera and 26 families in Qiqihar; 180 of which, from 55 genera and 24 families, were angiosperms, accounting for 97.30%. The predominant forms were deciduous and erect shrubs, and monotypic and oligotypic genera were the main genera of families. The floristic composition of the genus was complex, and the temperate floristic composition (82.46%) was absolutely dominant, especially the northern temperate floristic flora (49.12%), which highlighted the temperate floristic characteristics of this area. Ornamental shrubs held the highest economic value among shrub resources, followed by medicinal, raw (oil) material, and edible shrub species. However, much of their potential value remained untapped. Through screening, 10 edible economic shrubs suitable for the development of this area were proposed. [Conclusion] The shrub resources in Qiqihar are abundant in species, distributed across various families and genera, complex in floristic composition, and diverse in economic potentiality. Edible shrub plants can be utilized to develop a regional characteristic shrub industry.